Spinal Arachnoid Cyst in Children - Wihasto Suryaningtyas (Neurologico Spinale Medico Chirurgico, 2018)
Spinal arachnoid cyst is rarely seen in children. The presenting features can be mistakenly assumed as myelitis or Guillan-Barre syndrome. Intermittent weaknesses of the leg, progressive ascending weakness of the leg, sensory disturbance, and altered physiological reflexes are the hallmark of the disease. Nabors classified the pathology of the spinal arachnoid cyst into three types: extradural without nerve root involvement; extradural with nerve root; and intradural. It is mostly located in mid- to lower thoracic. The causes and natural history of pediatric arachnoid cysts are unclear. They usually are associated with trauma, surgery, arachnoiditis, and neural tube defects. MRI is a useful diagnostic tool. We present two cases of extradural and intradural arachnoid cysts in children. The follow-up and surgical results are reviewed. The surgical therapy itself is straightforward. However, the wrong conclusion might cause a financial burden and may cause preventable sequel.